Analisis Faktor Internal dan Eksternal Usaha Mikro melalui Pendekatan SWOT: Studi Kasus pada Bawang Goreng Bu Alba - Winda Astuti; Daspar Daspar (BISMA : Business and Management Journal, 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) of Bawang Goreng Bu Alba, a local-based snack microenterprise located in Bekasi Regency, Indonesia. The research employed a descriptive qualitative approach with a case study method. Data were collected through direct interviews and observations with the business owner and analyzed using SWOT, IFE (Internal Factor Evaluation), and EFE (External Factor Evaluation) matrices. The results show that the internal strength score is 3.04, while the weakness score is 1.72. On the external side, the opportunity score is 2.94, and the threat score is 1.84. The total SWOT score indicates the business is positioned in Quadrant I, suggesting an aggressive strategy. Therefore, Bawang Goreng Bu Alba is encouraged to optimize its strengths and opportunities through product innovation, digital promotion, and collaboration with influencers and marketplaces to enhance competitiveness and business sustainability.